Impairment of neutrophil migration to remote inflammatory site during lung histoplasmosis - Medeiros, Alexandra Ivo de [UNESP]; Secatto, Adriana; Belanger, Caroline; Sorgi, Carlos Artério; Borgeat, Pierre; Marleau, Sylvie; Faccioli, Lucia Helena (Hindawi Publishing Corporation, 2015)
Histoplasma capsulatum (Hc) induces a pulmonary disease in which leukotrienes promote activation and recruitment of effectors cells. It is also well-recognized that leukotriene B 4 (LTB 4) and platelet-activating factor (PAF) induce leukocyte recruitment to inflammatory sites. We investigated the impact of pulmonary Hc infection on PMN migration to a remote inflammatory site. Our results show that pulmonary Hc infection impairs LTB4- or PAF-stimulated PMN recruitment to air pouch. Yet, remote inflammation did not modify PMN numbers in the bronchoalveolar lavage fluid (BALF) of Hc-infected mice. Interestingly, the concomitant administration of PAF and LTB 4 receptor antagonists inhibited PMN recruitment to both BALF and the remote site, demonstrating cooperation between both mediators. Along that line, our results show that PAF-elicited PMN chemotaxis was abrogated in 5-lipoxygenase-deficient animals. These results suggest caution in the indiscriminate use of anti-inflammatory drugs during infectious diseases.